Learning from COVID-19: government leaders' perspectives to improve emergency risk communication - Elena Savoia; Rachael Piltch-Loeb; Eva H. Stanton; Howard K. Koh (BMC, 2023)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic highlighted the challenges of effective emergency risk communication (ERC) to protect public health, including the difficulty in tackling the spread of inaccurate information. This study aimed to understand those challenges and potential solutions by interviewing leading government spokespersons and their advisors from around the world with experience during large scale emergencies. Interviews were conducted with 27 individuals representing governments from 19 countries across five continents. Thematic analysis, using both a deductive and inductive approach, organized and identified salient themes and patterns that emerged from the interview data. Results The thematic analysis of the interviews' data led to the identification of 9 principles of communication: 1) Timeliness, 2) Transparency, 3) Coordination, 4) Accuracy and Consistency, 5) Accountability and Integrity, 6) Independence from politics, 7) Responsiveness, 8) Equity, 9) Trust and Empathy. We also developed 36 recommendations actionable by government agencies to enhance the practice of the 9 principles. Examples include the need for: proactive communication strategies, permanent communication task forces integrated into preparedness and response efforts, robust processes to enhance open discussion of controversial topics within government agencies, clarification of how various branches of government coordinate to oversee specific aspects of the overall communication, and development of relationships across public and private entities ahead of a crisis. Conclusions Our findings suggest key practical recommendations for leaders of government agencies to enhance ERC capabilities going forward. Before a crisis, they must constantly review internal processes and integrate ERC functions into overall communication planning efforts. During a crisis, they must coordinate roles and responsibilities across branches of governments, strive to communicate to a range of populations to uphold equity, maintain transparency by avoiding information voids on controversial issues and build trust by building relationships with a variety of community leaders. After a crisis, government agencies should continue the practice of social listening to hear more about the public's informational needs, strengthen civic participation processes, and understand how an always evolving information environment can best be leveraged during future crises.